Long-Term Humoral Response After a Second Dose of SARS-CoV-2 mRNA Vaccine in Japanese Kidney Transplant Recipients - Ohki, Yutaro; Kawabe, Mayuko; Yamamoto, Izumi; Katsumata, Haruki; Nakada, Yasuyuki; Kobayashi, Akimitsu; Urabe, Fumihiko; Miki, Jun; Yamada, Hiroki; Kimura, Takahiro; Matsuo, Nanae; Tanno, Yudo; et al. (Frontiers in Microbiology, 2022)
Background: The mortality rate due to coronavirus disease 2019 (COVID-19) in kidney transplant recipients (KTRs) is 16.8–32%. Vaccination against COVID-19 is expected to contribute to the prevention of infection, severe disease, and mortality; however, it has been reported that the humoral response to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mRNA vaccine in KTRs is poor. Vaccination strategies against COVID-19 vary from country to country, and in Japan, the third dose is given six months after the second dose. Few studies have evaluated long-term humoral responses after the second dose of SARS-CoV-2 mRNA vaccine. In addition, the superiority of BNT162b2 vaccine and mRNA-1273 vaccine in KTRs regarding humoral response is controversial. Methods: Ninety-four KTRs were administered a second dose of the BNT162b2 or mRNA-1273 vaccines, and anti-spike (anti-S) and anti-nucleocapsid (anti-N) SARS-CoV-2 antibody levels were measured 5 months (149.2 ± 45.5 days) later. The cutoff value of anti-S antibodies was defined ≥ 50 AU/mL and 1.4 Index for anti-N antibodies. The primary outcome was the rate of seropositivity, and factors associated with an appropriate humoral response were assessed by univariate and multivariate analysis. Results: Of 94 KTRs, only 45 (47.9%) patients were positive for anti-S antibodies. The median anti-S SARS-CoV-2 IgG antibody titers was 35.3 (Interquartile range 3.8–159.7). Anti-N SARS-CoV-2 IgG antibodies in all patients were <1.4 Index. Response to SARS-CoV-2 mRNA vaccines were 43.2% and 65% for BNT162b2 and mRNA-1273, respectively (p = 0.152). In comparison to high-dose, low-dose of mycophenolic acid was a robust factor associated with an adequate humoral response. Conclusions: The long-term humoral response after a second dose of SARS-CoV-2 mRNA vaccine in Japanese KTRs was poor. In comparison to high-dose, low-dose mycophenolic acid was related to an appropriate humoral response. Five months is too long to wait for a 3rd dose after 2nd dose of SARS-CoV-2 vaccine in KTRs. In this cohort, there was no statistical difference in humoral response to the BNT162b2 and mRNA-1273 vaccines. Additional large observational studies and meta-analyses are needed to clarify the factors related to an appropriate humoral immune response to COVID-19 vaccination.